The Influence Of Health Service Quality On The Satisfaction Level Of BPJS Patients At Cahaya Negeri Health Center - Irawan, Sendi Iklas Dede; Lorita , Evi; Saputra, Harius Eko (Social Sciences Journal, 2025)
This study aims to determine the influence of health service quality on the satisfaction levels of BPJS patients at Cahaya Negeri Health Center. The research employs a quantitative descriptive method, with data collected through questionnaires and documentation. The data analysis techniques include descriptive analysis, Product Moment correlation, simple linear regression, and hypothesis testing using the Determination Test (r²) and t-test. The findings indicate a very strong correlation between health service quality and patient satisfaction, with the influence value reaching 84.9%. This result demonstrates that the better the quality of health services provided, the higher the level of satisfaction among BPJS patients.